Environmental Health Risk Analysis of Sulfur Dioxide (SO2) Exposure in Ambient Air on Lung Function of Officers and Communities Around Public Fuel Filling Stations (SPBU) - Rahman Tri Cahyono; Elvi Sunarsih (Indonesian Journal of Global Health Research, 2024)
Air pollution is a serious problem globally, especially in urban areas where the transportation sector is one of the main contributors to sulfur dioxide (SO₂) emissions. Public filling stations (SPBU) that are centers of vehicle activity can produce SO₂ in ambient air that endangers lung function for individuals exposed in the long term, including workers and the surrounding community. This study examines SO₂ exposure at gas stations in Ogan Ilir Regency that can have an impact on health. The research method used two research methods, namely environmental health risk analysis (EHRA) with a deterministic approach and environmental health epidemiology with a cross-sectional approach. Sampling was conducted on 78 respondents using the Total Sampling method and air measurements using the Impinger Air Sampler tool. The average SO₂ concentration in the three gas station locations was 30,0 µg/m³ which exceeds the safe threshold. The daily intake level was 0,003 mg/kg/day, higher than the safe reference concentration (RfC) of 0.025 mg/kg/day, with a Risk Quotient (RQ) of 0,12, does not present a significant health risk. Furthermore, the results showed that impaired lung function was found in 73 respondents (93.6%), additional risk factors such as smoking habits and medical history were found to affect respiratory health. This research shows that there is no significant relationship between body weight, exposure, smoking, history of disease, or allergies and impaired lung function of officers and the community around the Ogan Ilir gas station.